2003
DOI: 10.1111/j.1349-7006.2003.tb01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Polo‐like kinase 1 (PLK1) is overexpressed in primary colorectal cancers

Abstract: PLK (polo-like kinase), the human counterpart of polo in Drosophila melanogaster and of CDC5 in Saccharomyces cerevisiae, belongs to a family of serine/threonine kinases. It is intimately involved in spindle formation and chromosome segregation during mitosis. The purpose of this study was to determine whether PLK1 is overexpressed in primary colorectal cancer specimens as compared with normal colon mucosa and to assess its relation to other kinases as a potential new tumor marker. In the present study, immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
167
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(184 citation statements)
references
References 25 publications
14
167
3
Order By: Relevance
“…However, Sak transcripts were only modestly increased in human colorectal cancer tissue (T), as compared with adjacent normal mucosa (NM) (T : NM ratio of 1.3170.10, mean7s.e.m., n ¼ 71) . Analysis of Plk1 transcripts in the same specimens showed a mean T : NM ratio of 1.6270.13, consistent with reports of Plk1 overexpression in colorectal and other primary cancers (Wolf et al, 1997;Macmillan et al, 2001;Takahashi et al, 2003). Interestingly, a small group of colorectal cancer patients showed Sak transcript levels more than 2SD below the mean, without an associated reduction in Plk1 expression.…”
Section: Sak Expression In Human Cancersupporting
confidence: 87%
“…However, Sak transcripts were only modestly increased in human colorectal cancer tissue (T), as compared with adjacent normal mucosa (NM) (T : NM ratio of 1.3170.10, mean7s.e.m., n ¼ 71) . Analysis of Plk1 transcripts in the same specimens showed a mean T : NM ratio of 1.6270.13, consistent with reports of Plk1 overexpression in colorectal and other primary cancers (Wolf et al, 1997;Macmillan et al, 2001;Takahashi et al, 2003). Interestingly, a small group of colorectal cancer patients showed Sak transcript levels more than 2SD below the mean, without an associated reduction in Plk1 expression.…”
Section: Sak Expression In Human Cancersupporting
confidence: 87%
“…Overexpression of these kinases can be observed in tumors and correlated with centrosome amplification and aneuploidy. 30,31 Members of the transforming acidic coiled-coil (TACC) family of proteins are implicated in cancer and have been shown to be concentrated at centrosomes, where they regulate microtubule stability. 32 The only shared structural feature among these proteins is their C-terminal ϳ200 amino acid long coiled coil region that is involved in the interaction with microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that elevated expression of Plk1 was observed in 57 (73.1%) of 78 primary colorectal cancers, statistically significant associations being evident with pT (primary tumor invasion) (P ¼ 0.0006), pN (regional lymph nodes) (P ¼ 0.008), and the Duke's classification (P ¼ 0.0005) (Takahashi et al, 2003).…”
Section: Colorectal Cancermentioning
confidence: 98%